Coffee Chlorogenic Acids Incorporation for Bioactivity Enhancement of Foods: A Review - Alexis Rojas-González; Claudia Yuritzi Figueroa-Hernández; Oscar González-Rios; Mirna Leonor Suárez-Quiroz; Rosa María González-Amaro; Zorba Josué Hernández-Estrada; Patricia Rayas-Duarte (Molecules, 2022)
The demand of foods with high antioxidant capacity have increased and research on these foods continues to grow. This review is focused on chlorogenic acids (CGAs) from green coffee, which is the most abundant source. The main CGA in coffee is 5-O-caffeoylquinic acid (5-CQA). Coffee extracts are currently the most widely used source to enhance the antioxidant activity of foods. Due to the solubility of CGAs, their extraction is mainly performed with organic solvents. CGAs have been associated with health benefits, such as antioxidant, antiviral, antibacterial, anticancer, and anti-inflammatory activity, and others that reduce the risk of cardiovascular diseases, type 2 diabetes, and Alzheimer’s disease. However, the biological activities depend on the stability of CGAs, which are sensitive to pH, temperature, and light. The anti-inflammatory activity of 5-CQA is attributed to reducing the proinflammatory activity of cytokines. 5-CQA can negatively affect colon microbiota. An increase in anthocyanins and antioxidant activity was observed when CGAs extracts were added to different food matrices such as dairy products, coffee drinks, chocolate, and bakery products. The fortification of foods with coffee CGAs has the potential to improve the functionality of foods.